International migration and movement of doctors to and within OECD countries - 2000 to 2018 Developments in countries of destination and impact on countries of origin - Socha-Dietrich, Karolina (OECD Publishing, 2021)
This paper presents the most recent data on the number of migrant doctors in the health workforce in the OECD countries, as well as the impact these regular migration flows have on the countries of origin, including an analysis of the developments since 2000. The objective of this paper is to inform policy dialogue at the national and international levels. The share of migrant doctors has continued to rise over the last two decades across the OECD countries, with around two-thirds of all foreign-born or foreign-trained doctors originating from within the OECD area and upper-middle-income countries. The lower-middle-income countries account for around 30% and low-income countries for 3-4% of the foreign-born and 4% of the foreign-trained doctors. In countries of origin that are large, migration to (other) OECD countries has a moderate impact, but some of the relatively smaller countries or those with weak health systems experience significant losses of (needed) health professionals
Keywords: Social Issues/Migration/Health